2004
DOI: 10.1002/nau.20019
|View full text |Cite
|
Sign up to set email alerts
|

Direct inhibition of rat detrusor muscle contraction by erythromycin

Abstract: PurposeDetrusor instability is a common problem in the elderly, which is usually treated with anti-cholinergic medication. This study investigates the effect of erythromycin on rat detrusor muscle contractile response to characterise its potential as an alternative inhibitor of bladder muscle contraction. Materials and MethodsStrips of rat detrusor muscle were suspended in a perfusion organ bath. The ResultsErythromycin 5 × 10 -4 M inhibited the maximum contractile response to EFS, carbachol and potassium by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The effect of tilmicosin phosphate on the intestinal motility of isolated rabbit duodenum revealed that tilmicosin phosphate inhibited the intestinal contractility in a dose dependent manner. These results were came in accordance with [52,53] who found to erythromycin macrolide antibiotic possess a concentration-dependent relaxant effects on the above intestinal parts but in different degree of intensity besides, erythromycin inhibits rat muscles contraction through the inhibition of calcium in lux and the modulation of intracellular calcium movement so depending on these data this might be also the same cause of the inhibitory effects of tilmicosin as reported by [54]. In the same way, [55] stated that azithromycin has a concentration-dependent, epithelium-independent, direct relaxant effect on muscles.…”
Section: Discussionsupporting
confidence: 90%
“…The effect of tilmicosin phosphate on the intestinal motility of isolated rabbit duodenum revealed that tilmicosin phosphate inhibited the intestinal contractility in a dose dependent manner. These results were came in accordance with [52,53] who found to erythromycin macrolide antibiotic possess a concentration-dependent relaxant effects on the above intestinal parts but in different degree of intensity besides, erythromycin inhibits rat muscles contraction through the inhibition of calcium in lux and the modulation of intracellular calcium movement so depending on these data this might be also the same cause of the inhibitory effects of tilmicosin as reported by [54]. In the same way, [55] stated that azithromycin has a concentration-dependent, epithelium-independent, direct relaxant effect on muscles.…”
Section: Discussionsupporting
confidence: 90%
“…One report has associated recent use of nonsteroidal antiinflammatory drugs with onset of acute retention 86 . Other compounds, ranging from erythromycin 87 to St. John's Wort (Hypericum perforatum) , 88 inhibit detrusor contractility in vitro, yet the clinical relevance of muscle strip studies, particularly when high drug concentrations are studied, remains unclear. Case reports of urinary retention induced by potent psychoactive drugs (fluoxetine‐risperidone) 89 and sympathomimetic recreational drugs (“ecstasy”: methamphetamine) 90 also exist.…”
Section: Management Issuesmentioning
confidence: 99%